2011
DOI: 10.1111/j.1834-7819.2011.01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between different genotypes of human cytomegalovirus and Epstein‐Barr virus and peri‐implant tissue status

Abstract: Background: The purpose of this study was to estimate the prevalence of different genotypes of human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV) in peri-implantitis and mucositis sites, and to evaluate the correlation between herpesvirus presence and clinical parameters. Methods: A total of 80 dental implants (mean time of loading, 4.16 ± 1.8 years) were evaluated during the course of the study (30 peri-implantitis, 25 mucositis and 25 healthy peri-implant sites). The following clinical parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(87 citation statements)
references
References 27 publications
(41 reference statements)
3
83
1
Order By: Relevance
“…Only 2 of 4 HCMV gB genotypes were detected in periapical lesions, gB-I and gB-II. Our results are in accordance with previously reported occurrence of HCMV gB genotypes in generalized chronic periodontitis and periimplantitis tissues (25,26). Similarly, these studies reported the absence of HCMV gB-III and gB-IV in their samples.…”
Section: Clinical Researchsupporting
confidence: 96%
See 2 more Smart Citations
“…Only 2 of 4 HCMV gB genotypes were detected in periapical lesions, gB-I and gB-II. Our results are in accordance with previously reported occurrence of HCMV gB genotypes in generalized chronic periodontitis and periimplantitis tissues (25,26). Similarly, these studies reported the absence of HCMV gB-III and gB-IV in their samples.…”
Section: Clinical Researchsupporting
confidence: 96%
“…Our results also corroborate some previous findings regarding EBV genotypes in oral pathologies. Wu et al (25) reported the presence of both EBV genotypes in tissue samples of generalized chronic periodontitis, with significantly higher frequencies of EBV-1, whereas Jankovic et al (26) found that EBV-1 was more frequent in samples of periimplantitis and mucositis compared with EBV-2. The occurrence of EBV-2 has been mostly found in immunocompromised patients such as HIV-infected and transplant recipients (24).…”
Section: Clinical Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…7,11,16 This study established nonsignificant difference in prevalence of HSV-1 between PI and HI, disagreeing with the outcome reported by the study mentioned above. Such discrepancy can be explained by two possible facts: The sample size in the present study counted 40 patients with 77 implants affected by PI, i.e., roughly 3-fold greater than in the previous studies that counted 20 to 30 PI cases.…”
Section: Discussioncontrasting
confidence: 56%
“…The association of titanium and zirconia as abutment materials, and the colonization of HCMV‐1 and EBV‐1 in clinically‐normal peri‐implant sites, has not been addressed in the literature. Few studies have determined the prevalence of EBV‐1 and HCMV‐1 in the subgingival plaque of patients with peri‐implantitis . The present study determined the prevalence of EBV‐1 and HCMV‐1 in submarginal plaque from titanium and zirconia abutment‐restored implant sites in the same individuals, thus facilitating a more direct comparison of the effect of the abutment material and eliminating inter‐participant variability in plaque biofilm characteristics, plaque‐control measures, and maintenance care.…”
Section: Discussionmentioning
confidence: 96%